Third-generation site characterization: cryogenic core collection, nuclear magnetic resonance, and electrical resistivity - Kiaalhosseini, Saeed, author; Sale, Thomas, advisor; Blotevogel, Jens, advisor; Johnson, Richard, committee member; Butters, Gregory, committee member (Colorado State University. Libraries, 2016)
To view the abstract, please see the full text of the document.
Keywords: electrical resistivity; nuclear magnetic resonance; unconsolidated sediment; non-aqueous phase liquid; cryogenic core collection; site characterization